State-level factors influencing tobacco cessation quitline spending in 2008 - Beyer, Eric J. (2010)
Tobacco cessation quitlines are an effective population-based smoking cessation treatment. However, quitline funding varies widely. Analyzing state-level factors may help explain these differences. We used data from the North American Quitline Consortium's 2008 survey of state quitlines and U.S. Census estimates to calculate per capita spending on quitline services. Publicly available data sources were used to identify demographic, tobacco use, tobacco control spending, and political and economic climate variables for the analysis. Linear regression analyses were used to identify potential predictors of per capita quitline services budgets in 2008. States with a greater percentage of their population with at least a high school degree, and states that spent more per capita on tobacco control programs overall, spent more per capita on quitline services (p > 0.05). In multivariate analysis, only per capita tobacco control expenditures was statistically significant (β=0.73, p =0.00, 95%CI 0.11-0.19). It appears that per capita tobacco control expenditures is the most consistent predictor of state per capita quitline expenditures. Additional research into whether and how state-level factors influence quitline funding levels is needed to allow advocates and policy-makers to understand better how to advocate for ongoing support of these population-based services.